Corporate Risks and The Impact on Earnings Management - I Gusti Ayu Purnamawati; Saarce Elsye Hatane (AKRUAL: JURNAL AKUNTANSI, 2022)
This study aims to determine the effect of corporate risk factors including debt contract motivation, employee diff, and litigation risk on earnings management in manufacturing companies in Indonesia. Data were collected from 100 manufacturing companies in Indonesia with purposive sampling so that 300 samples were obtained from 2017-2019. Multiple linear regression analysis is used to test earnings management in manufacturing companies in Indonesia by analyzing the debt contracts motivation, employee diff, and litigation risk. The results show that three variables in this study, namely debt contract motivation, employee diff, and litigation risk have a significant effect on earnings management. This study uses the litigation risk variable as a corporate risk factor that can encourage managers to report company finances more conservatively manner. Litigation risk has the potential to incur significant costs for dealing with legal issues. Rationally, managers will avoid losses due to litigation by conservatively presenting financial statements, because the profits are too high